Glaheng and Sewugalur: Developing a Da'wah Center and Religious Relations in Adikarto in the Early 20th Century - Athoillah, Ahmad (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
Research on the center of Islamic da'wah in Adikarto during the early 20th century, particularly in Glaheng and Sewugalur, is necessary as there is a shortage of historiographic studies dedicated to this topic. The primary objective for conducting this research is to elucidate the pivotal role of the Glaheng and Sewugalur communities in da'wah efforts to propel Islamic teachings and movements in Adikarto up to Indonesia's independence period. This investigation is crucial to enhance the historiography of Islamic societies' social activism in advancing teachings and religious movements. The study utilized the historical research method, employing Max Weber's religious relations approach. The findings reveal Glaheng and Sewugalur as pivotal centers of Islamic preaching in Adikarto, influenced by religious connections with the industrial economy. Furthermore, da'wah efforts in Glaheng and Sewugalur were undertaken to ensure that the religious significance of the Islamic community in Adikarto was not marginalized amidst the onset of modernity. Keywords: Glaheng, Sewugalur, Da’wah Center, Adikarto